Rekonstruksi Perlindungan Hukum Bagi Konsumen Perbankan di Tengah Ancaman Kejahatan Teknologi - Azis, Miftakul; Redi, Ahmad (Pascasarjana UDA, 2023)
Technological crimes in the banking sector, such as phishing, malware, and hacking, pose significant threats to customer data security and the integrity of banking institutions. This study aims to analyze the impact of technological crimes on customers and the banking industry, and explore the challenges faced by banking institutions in dealing with these threats. The study findings show that technological crimes not only result in direct financial losses for customers, but also threats to privacy and public trust in banking institutions. On the other hand, banks face reputational losses, legal liabilities, and high risk mitigation costs, including investment in security systems and recovery from crime incidents. This study suggests the need for improved banking security systems, collaboration between the banking sector, government, and the community, and broader digital education to reduce the negative impact of technological crimes in the banking sector.